2021
DOI: 10.37870/joqie.v11i18.272
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Principals’ Intellectual Stimulation on Students’ Performance at Kenya Certificate of Secondary Education in Public Secondary Schools, Kenya

Abstract: Transformational leadership is an ideal characteristic which enables the principals to engage with followers and raise consciousness about the significance of specific outcomes and new ways in which those outcomes might be achieved. The purpose of this study was to investigate the influence of principals’ intellectual stimulation on student academic performance in Kenya Certificate Secondary Examination (K.C.S.E) in Makueni County, Kenya. The objective that guided the study was to: assess how the principals’ i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…Somehow, these findings were negated. A researcher [30] investigated the influence of principals' leadership behavior on students' performance in a certification examination. They found that the principals scored higher in consideration than initiating structure.…”
Section: Correlation Analysesmentioning
confidence: 99%
“…Somehow, these findings were negated. A researcher [30] investigated the influence of principals' leadership behavior on students' performance in a certification examination. They found that the principals scored higher in consideration than initiating structure.…”
Section: Correlation Analysesmentioning
confidence: 99%
“…Moreover, within the framework of transformational leadership, leaders' inspirational motivation is of particular interest in the context of change management. Leaders who excel in inspirational motivation are adept at communicating a compelling vision, instilling a sense of purpose, and inspiring commitment (Musyoki, 2022). These qualities can be vital in addressing the emotional and motivational aspects of employee resistance to change, as employees are more likely to embrace change when they perceive it as meaningful and aligned with their values (Ouko, 2022).…”
Section: The Role Of Transformational Leadership On Employee Resistan...mentioning
confidence: 99%
“…Transformational leaders are often described as mentors or role models as they lead by example, encouraging an environment where innovative thinking is aligned with the values, beliefs and objectives of the organization. Individuals are openly recognised for their contributions in change commitment, thereby reducing resistance to change (Musyoki, 2022). Bass and Avolio (1994) developed an entire model for dimensions and components of transformational leadership which helps in reducing employee resistance to change.…”
Section: The Role Of Transformational Leadership On Employee Resistan...mentioning
confidence: 99%
“…Thus, this study considered a more holistic approach to understand the complex dynamics between inspirational motivation, and overall job satisfaction among the teachers. Musyoki (2021) conducted a study on Influence of Principals' Inspirational Motivation on students' Performance in Public Secondary Schools, in Makueni County, Kenya. The sample comprised of 111 principals, 729 teachers, and 12 Ministry of Education officials drawn from 388 secondary schools.…”
Section: Literature Review and Knowledge Gapmentioning
confidence: 99%